Pediatric gliosarcoma with fibrosarcomatous differentiation: Report of a rare case - Shantha Ravisankar; R Vimal Chander; Prem Kumar Devadoss (Wolters Kluwer Medknow Publications, 2012)
Gliosarcoma is a rare variant of glioblastoma with a biphasic pattern showing glial and mesenchymal differentiation. It is seen in adults during their fifth to sixth decades of life and is extremely rare in children. We report a case of primary gliosarcoma with fibrosarcomatous differentiation in an 11-year-old boy presenting with headache and vomiting. Imaging showed a contrast-enhancing isodense space-occupying lesion with areas of calcification in the right temporoparietal cortex. A total excision was done and, on histopathologic examination, a differential diagnostic consideration of gliosarcoma and teratoma with malignant transformation was made. After immunohistochemical analysis, a final diagnosis of gliosarcoma with fibrosarcomatous differentiation was then made. Primary gliosarcoma is a very rare tumor in children with a poor prognosis.